2003
DOI: 10.1097/01.mp.0000089778.48167.91
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HER2 and C-KIT in Nasopharyngeal Carcinoma: Implications for a New Therapeutic Approach

Abstract: We sought to determine the expression and prognostic significance of HER2 and c-KIT proteins in nasopharyngeal carcinoma (NPC). In this retrospective study, immunohistochemical stains for HER2 and c-KIT were performed on formalin-fixed paraffin-embedded sections from 49 patients with NPC who were treated at our hospital from 1971 to 2000. The clinical and immunohistochemical data were correlated, including gender, ethnic origin, age, histological type, EBV status (EBER in situ hybridization), stage, and overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 26 publications
2
23
1
Order By: Relevance
“…The survival analyses for the c-kit expression have been demonstrated in several malignant tumours (Tonary et al, 2000;Bar-Sela et al, 2003;Scobie et al, 2003;Krams et al, 2004;Simon et al, 2004;Pan et al, 2005), while there was only one survival analysis (Simon et al, 2004) regarding breast cancer, in which no difference was found in the survival between the patients with or without the c-kit expression. Although no statistically significant difference in clinical outcomes has been found in endometrial adenocarcinomas (Scobie et al, 2003), nasopharygeal carcinomas (Bar-Sela et al, 2003) and small cell carcinomas of the urinary bladder (Pan et al, 2005), two studies on ovarian cancers (Tonary et al, 2000) and neuroblastomas (Krams et al, 2004) indicated an association between a loss of the c-kit expression and poor prognosis. In ovarian cancers, the loss of c-kit expression was associated with a poor prognosis, while the c-kit expression tended to decrease at an advanced stage (Tonary et al, 2000), being similar with our findings in breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The survival analyses for the c-kit expression have been demonstrated in several malignant tumours (Tonary et al, 2000;Bar-Sela et al, 2003;Scobie et al, 2003;Krams et al, 2004;Simon et al, 2004;Pan et al, 2005), while there was only one survival analysis (Simon et al, 2004) regarding breast cancer, in which no difference was found in the survival between the patients with or without the c-kit expression. Although no statistically significant difference in clinical outcomes has been found in endometrial adenocarcinomas (Scobie et al, 2003), nasopharygeal carcinomas (Bar-Sela et al, 2003) and small cell carcinomas of the urinary bladder (Pan et al, 2005), two studies on ovarian cancers (Tonary et al, 2000) and neuroblastomas (Krams et al, 2004) indicated an association between a loss of the c-kit expression and poor prognosis. In ovarian cancers, the loss of c-kit expression was associated with a poor prognosis, while the c-kit expression tended to decrease at an advanced stage (Tonary et al, 2000), being similar with our findings in breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of PDGF receptor and c-kit has also been detected in NPC tumors, cell lines or tumor xenograft [24][25][26][27]. Although the functional involvement of these receptors in NPC tumorigenesis remains to be elucidated in details, a preclinical study with STI571 (imatinib mesylate, with known inhibitory activity against the tyrosine kinase abl, or the chimeric bcr-abl, as well as PDGF receptor and c-kit) [26] showed that it can inhibit NPC cell growth as well as c-kit activation.…”
Section: Introductionmentioning
confidence: 97%
“…C-kit is a transmembrane growth factor receptor for stem cell factor which is not expressed in normal nasopoharyngeal epithelial cells. 5 It was expressed in one-third of NPC's restricted to case of EBV positive undifferentiated on non-keratnizing carcinoma. In this case, C-kit / CD117 was negative.…”
Section: Discussionmentioning
confidence: 99%